Tougher educational exam leading to worse selection - Eduardo de Carvalho Andrade; Luciano I. de Castro (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
A parallel of education with transformative processes in standard markets suggest that a more severe control of the quality of the output will improve the overall quality of the education. This paper shows a somehow counterintuitive result: an increase in the exam diffculty may reduce the average quality (productivity) of selected individuals. Since the exam does not verify all skills, when its standard rises, candidates with relatively low skills emphasized in the test and high skills demanded in the job may no longer qualify. Hence, an increase in the testing standard may be counterproductive. One implication is that policies should emphasize alignment between the skills tested and those required in the actual jobs, rather than increase exams' diffculty.
Keywords: I2; J24; 330; school standard; signaling model; cognitive skill; noncognitive skill; Bildungsökonomik; Bildungsabschluss; Qualifikation